2000
DOI: 10.1074/jbc.m002571200
|View full text |Cite
|
Sign up to set email alerts
|

Selective Interaction of Complexin with the Neuronal SNARE Complex

Abstract: Complexins are evolutionarily conserved proteins that specifically bind to soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complexes and thus may regulate SNARE function. Using purified proteins, we have performed a detailed analysis of the structure of complexin and of its interaction with SNARE proteins. NMR spectroscopy revealed that isolated complexins have no tertiary structure but contain an unusual ␣-helical middle domain of approximately 58 amino acids that overlaps with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
190
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 169 publications
(211 citation statements)
references
References 43 publications
20
190
1
Order By: Relevance
“…These results are partially supported by evidence that syntaxin 2 coimmunoprecipitated with VAMP 2 from acinar cell membranes (36). Moreover, when evaluated in vitro using recombinant proteins, no association of complexin 1 or 2 with SNARE complexes containing syntaxin 4 was found (13,21), suggesting that the interaction with syntaxin 4 seen in acini may involve additional regulatory proteins.…”
Section: Discussionsupporting
confidence: 69%
“…These results are partially supported by evidence that syntaxin 2 coimmunoprecipitated with VAMP 2 from acinar cell membranes (36). Moreover, when evaluated in vitro using recombinant proteins, no association of complexin 1 or 2 with SNARE complexes containing syntaxin 4 was found (13,21), suggesting that the interaction with syntaxin 4 seen in acini may involve additional regulatory proteins.…”
Section: Discussionsupporting
confidence: 69%
“…As predicted by the structural data, the central ␣-helical region (aa 48 -70) was indispensable for the interaction with SNARE complexes (30,36,37). Site-specific mutations of the amino acids on CPX-I that are thought to contact the SNARE complex (R59H, R48A, R63A, and Y70A) showed a strong reduction in the binding capacity (Fig.…”
Section: Site-directed Mutagenesis Of Conserved Residues In Cpx-i -Imentioning
confidence: 94%
“…55 ). We found that the C 2 AB fragment displaces this complexin fragment from membrane-anchored SNARE complexes in the presence of Ca 2+ (ref.…”
Section: Structural Determinants Of Quaternary Sscap Complex Formationmentioning
confidence: 99%